Essentials of strength training and conditioning - Baechle, Thomas R.; Earle, Roger W. (Human Kinetics, 2008)
Essentials of Strength Training and Conditioning is the most comprehensive reference available for strength and conditioning professionals. In this text, 30 expert contributors explore the scientific principles, concepts, and theories of strength training and conditioning as well as their applications to athletic performance. Essentials of Strength Training and Conditioning is the most-preferred preparation text for the Certified Strength and Conditioning Specialist (CSCS) exam. The research-based approach, extensive exercise technique section, and unbeatable accuracy of Essentials of Strength Training and Conditioning make it the text readers have come to rely on for CSCS exam preparation. The third edition presents the most current strength training and conditioning research and applications in a logical format designed for increased retention of key concepts. The text is organized into five sections. The first three sections provide a theoretical framework for application in section 4, the program design portion of the book. The final section offers practical strategies for administration and management of strength and conditioning facilities.